1234. Racial Disparities in Invasive Staphylococcus aureus (iSA) Disease in Metropolitan Atlanta, a Population-Based Assessment, 2016. (26th November 2018) - Overton, Rahsaan; Fridkin, Scott; Tunali, Amy; Ray, Susan M
Abstract: Background: Disparities in incidence of invasive methicillin-resistant S. aureus (iMRSA) infections have been examined, suggesting that differences were in part driven by socio-economic factors. An analysis was conducted to determine whether similar disparities exist for invasive methicillin-susceptible S. aureus (iMSSA). Methods: The Georgia Emerging Infections Program (GA EIP) conducts active, population-based surveillance for iSA within the 8-county area of Atlanta. Cases were defined as residents of the surveillance area with SA isolated from a normally sterile site, with cultures within a 30-day period considered a single case. Age- and race-specific incidence were calculated using 2016 US census data; other/unknown race were excluded from analysis (<5% of cases). Incidence rate ratios (RR) between stratum and summary adjusted rate ratios (aRR) were calculated with the Mantel–Hanzel method. Results: During 2016, 1, 958 cases were identified (42% iMRSA and 58% iMSSA); crude incidence was 48.5/100, 000. Rates were highest among those ≥ 65 years of age for both blacks and whites (Figure 1). When compared with iMSSA, iMRSA incidence was consistently lower across all age groups (aRR: 0.7; 95% CI: 0.7–0.8) (Figure 2). However, the incidence of iMRSA among black cases was double that among white cases (aRR: 2.0; CI: 1.7–2.3) across all age groups. This racial disparity was less pronounced in iMSSA: among younger cases (<65 years old), iMSSA incidence among blacks was significantly higher than whites (aRR: 1.6; CI: 1.4–2.0), while rates were similar in older blacks and whites (≥65 years old) (aRR: 0.9; CI: 0.8–1.2). Bloodstream infections were the most common presentation overall; however, for iMSSA infections, joint/synovial infections were significantly less common among black cases than white cases (RR: 0.3; CI: 0.1–0.7). Conclusion: In the Atlanta area, racial disparities in iSA were noted, with higher incidence among blacks than whites for both iMSSA and iMRSA. The racial disparity is more extreme for iMRSA. Notably the racial disparity is not observed in cases age 65 and over. Causes for these disparities should be investigated. Disclosures: S. Fridkin, Pfizer Inc.: Grant Investigator, Research support.